Understanding Consumer Adoption of e-Pharmacy in India: The Role of Gender, Generation, Profession, and Area of Living - Chowdhury, Saptaparni Roy; Majumder, Jayeeta; Gangopadhyay, Sourav (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Convenience, accessibility and affordability are the three constructs that is attracting consumers to transform the healthcare landscape digitally into adoption of e-pharmacy. This research study probes into the ascendency of four major socio-demographic factors namely gender, generation, profession and area of living on the acceptance of e-pharmacy among Indian population framing the objectives in such a way that it determines in case these above-mentioned factors significantly influence the user adoption behaviour or not. Materials and Methods: A structured online questionnaire, inspired from SCRIBD was distributed through Google Forms keeping in mind a convenience sampling method. The total set of participants (n=431) is chosen from diverse demographic domains such as Gender, Generation, Profession and Area of Living keeping in mind their privacy, anonymity, and voluntariness in case of participation. Cronbach’s Alpha, Skewness, Kurtosis test was done to assure reliability and normal distribution, Levene’s Test to ensure homogeneity of variance, later Independent Sample t-test and One-Way ANOVA were conducted using IBM SPSS software. Results: The findings reveal that gender and area of living significantly influence e-pharmacy adoption, but in the same way profession and generation do not, implicating the prominent role of socio-geographical factors towards accepting or adopting digital healthcare platforms. Conclusion: Our research highlights the importance of targeted awareness campaigns and technological infrastructure advancements, especially in rural areas and also among particular gender groups, to uplift the adoption of e-pharmacy in India.
Keywords: Digital Healthcare; E-pharmacy; Gender; Generation; Profession; Area of Living; Technology